4th Electronics Packaging Technology Conference, 2002.
DOI: 10.1109/eptc.2002.1185668
|View full text |Cite
|
Sign up to set email alerts
|

Study of surface topography in nanometric ductile cutting of silicon wafers

Abstract: Email: xdliu@,SIMTech.a-star.edu.sq p. Subsurface damage in single-crystal silicon induced by ultraprecision grinding was evaluated by means of transmission electron microscopy (TEM) [4, 51. Dislocations appeared in the subsurface zone beneath the amorphous layer and penetrated from 100 nm to 600 nm. However, the AbstractNanometric ductile cutting experiments of silicon wafers have been carried out using an ultraprecision lathe with a single crystal diamond tool in this study. The machined silicon wafer surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Surface characteristics produced by DMC of brittle materials were experimentally studied extensively. It was found surface roughness obtained in DMC of silicon was much better than that generated from the grinding [55]. Very smooth surfaces and continuous chips can be achieved in DMC of silicon using an external high hydrostatic pressure of 400 MPa with a diamond tool having an edge radius at nanometer scale [21].…”
Section: Surface Finishmentioning
confidence: 89%
See 1 more Smart Citation
“…Surface characteristics produced by DMC of brittle materials were experimentally studied extensively. It was found surface roughness obtained in DMC of silicon was much better than that generated from the grinding [55]. Very smooth surfaces and continuous chips can be achieved in DMC of silicon using an external high hydrostatic pressure of 400 MPa with a diamond tool having an edge radius at nanometer scale [21].…”
Section: Surface Finishmentioning
confidence: 89%
“…Typically, the depth of subsurface damage on a silicon wafer induced by an ultra-precision grinding is around 1-3 mm [55]. The average subsurface damage depth imparted by a fine grinding process of silicon wafers is up to 6 mm [56].…”
Section: Subsurface Damagementioning
confidence: 99%
“…According to the indentation fracture mechanics, the condition of ductile regime cutting is that the cutting depth of grit is less than the critical cut depth d c of monocrystalline silicon. Until now, many studies have been reported on the ductile regime cut of monocrystalline silicon both experimentally and theoretically [4,5]. Brian P. O'Connor performed cutting tests using -45• rake angle diamond tools, results show that the critical chip thickness in monocrystalline silicon for ductile regime removal reaches a maximum of 0.12µm in the [100] direction [4].…”
Section: Study Of Brittle-ductile Transition Of Slicing Silicon Wafermentioning
confidence: 99%
“…Brian P. O'Connor performed cutting tests using -45• rake angle diamond tools, results show that the critical chip thickness in monocrystalline silicon for ductile regime removal reaches a maximum of 0.12µm in the [100] direction [4]. K.Liu carried out cutting experiments of monocrystalline silicon wafers along (111) direction, SEM observations indicates the max chip thickness of ductile cutting is 0.32µm [5].…”
Section: Study Of Brittle-ductile Transition Of Slicing Silicon Wafermentioning
confidence: 99%
“…Wafer slicing process is a key technology, the fixed-abrasive diamond wire saw(FADWS) machining technology, with some advantages of low kerf loss and clean working environment for slicing [1][2], is expected to be used for slicing hard-brittle materials such as silicon crystal widely in the future. In the past years, many studies reported that the material removal of single crystal silicon could be in a ductile regime by turning, grinding and lapping [3][4][5], and theoretical study indicated the silicon also could be sawed in a ductile regime possibly [1], but a complete clear understanding about material removal mechanisms in FADWS machining single crystal silicon has not been obtained. And the evidences of change on brittle-ductile transition of material removal are still deficient.…”
Section: Introductionmentioning
confidence: 99%